Great improvement in the performance and lifetime of a fuel cell using a highly dense, well-ordered, and cone-shaped Nafion array. Issue 11 (21st February 2020) - Ning, Fandi; Bai, Chuang; Qin, Jiaqi; Song, Yujiang; Zhang, Ting; Chen, Jiafan; Wei, Jun; Lu, Guanbin; Wang, Huihui; Li, Yali; Gu, Junnan; Shen, Yangbin; et al.
Abstract : Great improvement in a fuel cell was achieved by constructing three fast pathways using a highly dense, well-ordered, and cone-shaped Nafion array. Abstract : Proton exchange membrane fuel cells (PEMFCs) have potential applications in electric vehicles, laptops, and power stations. The catalyst layers in a membrane electrode assembly (MEA) are the core locations in PEMFCs in which to convert the chemical energy of fuels to electrical energy. For a catalyst layer with high performance, it must possess three fast transfer ways to transfer mass (reactants and products), electrons (e − ) and protons (H + ) quickly and simultaneously. In this work, we greatly improved the performance and lifetime of a fuel cell by constructing these three fast transfer pathways based on a well-ordered and cone-shaped Nafion array with a very high density (5.7 × 10 8 cones per cm 2 ) using an anodic aluminum oxide (AAO) template. To build a fast pathway for electron transfer, well-dispersed graphene nanosheets were further filled into the Nafion array. After a series of efforts based on the above, the performance of the fuel cell with a cone array as an anode reached 1240 mW cm −2, which is 2.5 times higher than that without an array. Since Pt loading was as low as 17.6 μg cm −2, the mass specific power of Pt was as high as 70.5 kW gPt −1 . Consequently, the Pt loading successfully reached the U.S. DOE 2020 target at the anode side, i.e. 25 μg cm −2 . In addition, the lifetime of the PEMFC with the cone array is at least 300 h, which is much longer than the 150 h for a PEMFC without an array. Therefore, this work fully exhibits the great potential advantages of using an ordered Nafion array, and is promising to promote the development of the next generation of MEA for use in PEMFCs.